Factors Associated with the Level of Mother's Knowledge About Toddler Nutrition in the Working Area of ​​the Ternate Health Center, Alor Regency - Eta, Yusrianto Azhari; Takaeb, Afrona E. L; Toy, Sarci Magdalena (Faculty of Public Health, Nusa Cendana University, 2023)
Age, information or mass media, education level, parity, economy or money, social culture, and environment are some of the causes of moms' lack of understanding regarding toddler nutrition. In the working area of the Ternate Health Center, Alor Regency, this study seeks to ascertain the association of age, education level, parity, and income on the degree of awareness of mothers about toddler nutrition. This kind of study is a cross-sectional quantitative analytic investigation. In June and July 2022, this study was carried out in the Ternate Health Center's operational space in the Alor Barat Laut District of Alor Regency. The 318 mothers who worked at the Ternate Health Center in the Alor Regency comprised the study's population. A sample of 76 participants was selected using a basic random sampling procedure. In this investigation, the chi-square test was applied with a significance threshold of 0.05. The findings indicated that the mother's degree of awareness on toddler nutrition was related to her variable level of education (0.000) and income (0.018). While there is no correlation between the variables age (0.460) and parity (0.923) and mothers' degree of knowledge regarding toddler nutrition. Toddler mothers are expected to make an effort on their own to improve nutrition education by being more diligent and active in bringing their children to posyandu or puskesmas so that mothers can make more use of healthcare facilities as a place to get health information, especially about toddler nutrition so they can provide appropriate care for toddlers and toddlers. Manage your weaving income to put more money aside for your kids' nutritional needs.